Lipoprotein(a) and LDL-Cholesterol Status in type 2 Diabetes Mellitus with Microvascular Complications (Bangladesh Journal of Medical Biochemistry, 2017)
The present study was conducted to investigate lipid profile in T2DM patients with microvascular complications such as nephropathy, retinopathy and neuropathy. Case-control observational study in Medical Research Unit (MRU), of Medical and Health Wealfare Trust (MHWT), Uttara, Dhaka, Bangladesh from October 2013 to December 2014; A total of 150 T2DM (Group-B) patients (male: 90, female: 60, age range: 25-65 years) with 30 patients in each sub-group, i.e. without complications (B1), with nephropathy (B2), with retinopathy (B3), with neuropathy (B4) and with multiple complications (B5) and 30 normal controls (male: 18, female: 12, age range: 28-60 years)(Group-A) were included in the study. The lipid profile i.e. triglyceride (TG,) total cholesterol (TC), LDL-C, HDL-C and Lp(a) were quantitatively measured by standard clinical laboratory methods. The findings were compared statistically among patients and controls. Serum lipids i.e. TG, TC, LDL-C and Lp(a) were elevated and HDL-C was decreased in patients (Group -B) compared to controls (Group-A) significantly [Group-A vs Group-B: TG (mg/dl) - 93.7±18.9, 184.4±36.5; TC (mg/dl) - 141.9±25.5, 237.7±69.5; LDL-C (mg/dl) - 85.8±22.1, 165.1±26.3; HDL-C (mg/dl) -47.4±17.4, 35.5±6.6; Lp(a) (mg/l) - 29.1±14.2, 73.5±23.4] (P< 0.001). Among microvascular complications, T2DM-patients with nephropathy (Group-B2) had the highest elevated levels of TG, TC, LDL-C and Lp(a) and maximally decreased level of HDL-C (P< 0.001); Our findings suggest that reduction of all cholesterol-bearing lipoproteins that contain apoprotein B would be important in T2DM with microvascular complications. Possibly Lp(a) reduction and induction of HDL-C are most relevant in this regard.Bangladesh J Med Biochem 2015; 8(2): 66-73